A study on thermal environmental performance in atria in the tropics with special reference to Malaysia - Abdullah, Abd Halid (2007)
This research investigated the thermal environmental performance of atria in the tropics. with special reference to Malaysia. The main design problems that affect the thermal and energy performance in existing Malaysian atria are overlighting and overheating due to the direct application of western top-lit atrium roof form. As such. this research proposed the side-lit atrium form which aimed at controlling direct sunlight as a way to improve thermal and energy performance of atria in the tropics. Based on the proposed conceptual atrium form, this research examined quantitatively some of the low energy design features and ventilation strategies that can possibly contribute to a better indoor thermal environmental perfonnance of atria in the tropics. The ultimate aim of this research is to propose design principles and guidelines for new low-energy atria in the tropics. The combined research methods are as follows: developing a conceptual low energy atrium form based on the vernacular design features to be used for computer modelling studies; calTying out field measurement and monitoring on an existing atrium building which provides validation data for dynamic thermal simulation program TAS: modelling exercise on the same monitored building using dynamic thermal modelling to develop confidence in cOlTectly modelling thermal stratification within the multi-level atrium: employing dynamic thermal modelling to model representative atrium forms (i.e. both side-lit and top-lit model) and examine quantitatively the effects of some of the key design parameters (i.e. wall-to-roof void area, roof overhangs, and internal solar blinds) on the thermal comfort and energy performance in atria due to both full natural ventilation and pressurised ventilation; and utilising computational Ouid dynamics (CFD) to complement the dynamic thermal simulation results, and to investigate quantitatively the thermal and ventilation performance within the atrium well in response to the changes of design parameters (i.e. varying the inlet to outlet opening area ratio and outlet" s alTangement). The research findings supported the research proposition and demonstrated the effectiveness of the side-lit form as a way to improve the thermal and energy performance with regard to users' thermal comfort in atria in the tropics. The main findings from both dynamic thermal simulation and computational Ouid dynamics (CFD) arc as follo\\s: full natural ventilation strategy is not viable for Ivlala\'sian atria: both suilicicnth hic:h \'.all- ......... .. .. ...... to-roof void area and extending high-level internal solar blinds can greatly improve the atrium's thermal performance particularly on occupied levels; sufficiently wide roof overhangs above the clerestory areas of the side-lit atrium form generally improves the thermal and energy performance within the central atrium throughout the year; reasonably comfortable thermal environment on occupied levels of a low-rise atrium can be achieved by only supplying cooler air at low-level with sufficient ventilation rate: sufficiently higher inlet to outlet opening area ratio can improve the thermal performance on the occupied levels; and with equal inlet and outlet opening area, changing the outlet" s arrangement (i.e. location and arrangement) would not significantly affect the atrium's thermal perforn1ance.